Letter - Stewart, Ronald
010-0074-001 SPANISH PEOPLE'S FRONT (London Information Bureau) Telephone: ABBEY 4857 3 VICTORIA STREET LONDON, S.W.1 17th. Oct. 1936. The Secretary, Trade Union Congress, Transport House, Smith Square. S.W.1. Dear Sir, We should be exceedingly glad if you would appoint one of your Executive to serve as a member of the "Co-ordinating Committee for Spanish Relief" which is now being formed. We wish it to be clearly understood that the object of this committee is not to interfere with the work which the various organisations are now doing for anti-fascist Spain, but rather to form a point of contact between them, so that each may know what the other is doing, thus making their work more effective by preventing overlapping. My colleague and I have been specially sent from Spain to work in this country; the committee has the approval of the Spanish Ambassador, Don Pablo de Azcarate, and the Earl of Listowel has kindly consented to be our president. The Spanish Medical Aid Committee is represented by Viscount Churchill. We are in direct touch with Spain and are constantly receiving photographs, posters, newspapers and other material, and we are confident you will agree that such a committee will be the best medium through which to distribute this propaganda to the various organisations. It is exceedingly important that both the Trade Union Congress and the Labour Party should co-operate with us, for your international contacts will greatly assist those other organisations which are without the same facilities as yourselves. Within a few days we shall notify you of the exact date of our next meeting. Should your appointed delegate not be available for any particular meeting, there is no reason why a substitute should not attend. Hoping to have your co-operation and valuable assistance in this matter, Yours faithfully, Ronald Stewart 292/946/10/79